2008
DOI: 10.1253/circj.cj-07-1006
|View full text |Cite
|
Sign up to set email alerts
|

Valuable Markers for Contrast-Induced Nephropathy in Patients Undergoing Cardiac Catheterization

Abstract: ontrast-induced nephropathy (CIN) is a recognized complication of both coronary angiography (CAG) and percutaneous coronary intervention (PCI), and is associated with prolonged hospitalization and adverse clinical outcomes. [1][2][3][4][5] Several risk factors for CIN have been identified: chronic kidney disease (CKD), diabetes mellitus (DM), congestive heart failure, intravascular volume depletion, and using a large amount of contrast media are important predisposing factors. 2-4 CKD is also a risk factor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 39 publications
(39 reference statements)
5
44
1
Order By: Relevance
“…The results of the present study are in agreement with the most results obtained by others reports Kato et al and Mehran et al [19][20][21][22][23][24][25][26][27]. In present study was found a highly significant increment in serum creatinine and cystatin C while decrease in eGFR 24 hours after angiography (p<0.001, 0.01) when compared between two groups (CIN+, CIN-).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results of the present study are in agreement with the most results obtained by others reports Kato et al and Mehran et al [19][20][21][22][23][24][25][26][27]. In present study was found a highly significant increment in serum creatinine and cystatin C while decrease in eGFR 24 hours after angiography (p<0.001, 0.01) when compared between two groups (CIN+, CIN-).…”
Section: Discussionsupporting
confidence: 93%
“…In present study was found a highly significant increment in serum creatinine and cystatin C while decrease in eGFR 24 hours after angiography (p<0.001, 0.01) when compared between two groups (CIN+, CIN-). This result is consistent with Wang et al, Liu et al and Nozue et al founded serum level of cystatin C is a reliable marker for CIN at 24 hours p<0.001 and serum creatinine increased significantly at 48 hours, also study carried by Wacker-Gussmann et al [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] found that cystatin C level and the cystatin C/creatinine ratio independently predict the risk of CIN in patients undergoing coronary angiography, but another study by Ribichini et al [32] found a significant increase in serum cystatin C concentrations 12 hours earlier than serum creatinine, therefore a rise of serum cystatin C at 12 hours from baseline was the earliest predictor of CIN than serum creatinine [18].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are similar to those of Kato et al, (2008) [27]; who found that urinary L-FABP levels were significantly increased after coronary angiography, suggesting transient proximal tubular damage by contrast medium, although the classical markers were not useful for predicting or detecting CIN. Another study carried out by BachorzewskaGajewska et al, (2009) [28]; supported this finding, where the 25 included patients underwent PCI; none of them fulfilled the criteria of contrast nephropathy, despite there was highly significant elevation of urinary L-FABP as early as 4 hours after contrast administration (25.90±21.93 pg/ml) and at 24 hours (33.49±26.41 pg/ml) compared to a baseline value of 3.76±1.52 pg/ml.…”
Section: -Fasting Plasma Glucose Level By Colorimetric Methodssupporting
confidence: 91%